2021
DOI: 10.1186/s12885-021-08181-0
|View full text |Cite
|
Sign up to set email alerts
|

Italian onco-haematological patients’ preferences in bad news communication: a preliminary investigation

Abstract: Background The manner in which bad news is communicated in oncological contexts can affect patients’ engagement, their coping strategies and therapeutic compliance. Although this topic has been broadly investigated since the nineties, to the best of our knowledge, little has been written about Italian patients’ experiences and preferences concerning what the oncologists should disclose and how they should intimate patients about their health conditions in different stages of oncological disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 76 publications
(77 reference statements)
2
9
0
Order By: Relevance
“…These discrepancies in perceptions may suggest that patients have higher expectations from doctor/nurse-patient communication, which aligns with the general trend of high consumers' expectations in all markets and particularly in the health industry (Shafei et al, 2019). This study confirms the findings of similar research that not enough satisfaction is reported for important factors in doctor-patient communication and mainly the requirement for using simple terminology (Bongelli et al, 2021;Kha and Piasecki, 2008), the little time devoted to information (Swallmeh et al, 2018;Pun et al, 2015), the non-sufficient dissemination of medical information to patients (Moret et al, 2008) and the lack of genuine interest in patients' health and life (Platonova and Shewchuk, 2015).…”
Section: Implications For Researchsupporting
confidence: 86%
See 4 more Smart Citations
“…These discrepancies in perceptions may suggest that patients have higher expectations from doctor/nurse-patient communication, which aligns with the general trend of high consumers' expectations in all markets and particularly in the health industry (Shafei et al, 2019). This study confirms the findings of similar research that not enough satisfaction is reported for important factors in doctor-patient communication and mainly the requirement for using simple terminology (Bongelli et al, 2021;Kha and Piasecki, 2008), the little time devoted to information (Swallmeh et al, 2018;Pun et al, 2015), the non-sufficient dissemination of medical information to patients (Moret et al, 2008) and the lack of genuine interest in patients' health and life (Platonova and Shewchuk, 2015).…”
Section: Implications For Researchsupporting
confidence: 86%
“…Communication in clinical practice should not only serve as a way for the professional to obtain information from patients about their pathology, IJHCQA 35,1 but also as a means of informing patients about their illness (Kha and Piasecki, 2008). The participants of this study also agree that the use of specialized terminology to convey information that the patient is unfamiliar with is a prohibiting factor to good communication, which may lead to passive behavior from the patient's side (Bongelli et al, 2021;Verlinde et al, 2012). Survey's participants also agree that patients' physical conditions are barriers to communication.…”
Section: Prohibitors To Good Comminationmentioning
confidence: 69%
See 3 more Smart Citations